Building a Digital Ecosystem: Educational Technology and Continuous Learning Innovation - Endah Pramiasih; Heri Yanto; Tri Joko Raharjo; Amin Pujiati (Universitas Negeri Semarang, 2026)
The digital transformation of education requires teachers to innovate and integrate technology effectively into learning, but its implementation in Indonesia faces systemic challenges related to school leadership, academic culture, and technological infrastructure. This study aims to analyze the determinants of teachers' digital innovation, focusing on the role of online self-training, academic culture through Learning Community (KOMBEL), principals' leadership, and information technology (IT) facilities. The quantitative approach uses Structural Equation Modeling (SEM) with a population of 2015 ASN teachers and then a random sample was obtained from 302 state junior high school teachers in four districts of the former West Pekalongan Residency. These findings reveal that the leadership of school principals significantly shapes academic culture (β=0.597) and the provision of IT facilities (β=0.644). IT facilities emerged as the dominant factor influencing teachers' digital innovation (β=0.462). The research model showed a good match with empirical data (CFI=0.997; RMSEA = 0.059). The study theoretically integrates the Technology Acceptance Model (TAM) which explains the acceptance of technology through the perception of convenience and benefit with the Resource-Based View (RBV) which analyzes the school's internal resources as a strategic asset for continued competitive advantage. In practical terms, these findings imply that the sustainable strengthening of the digital ecosystem requires integrated policies that simultaneously align transformational leadership, collaborative culture development, and investment in technology infrastructure.